Analysis of the Impact of Accounting Information Systems (AIS) on Organizational Effectiveness - Sow, Mouhamadou T (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The purpose of the study was to examine how AIS is observed by its users within an academic medical center where financial transactions are critical in managing patient care and research operations. A cross-sectional qualitative research design was applied using interviews, the convenience sampling method was used to select study participants, and a thematic analysis was conducted to identify patterns in the responses given. Based on the results provided in the interviews, 1) AIS design and specifications are associated with user satisfaction and performance in the workplace environment. 2) Organizations must focus on delivering AIS that offers the resources required for employees to perform their roles and being as effective as possible. 3) User needs should be identified as part of any AIS implementation or upgrade to support performance optimization with ongoing system utilization. The study questions were validated under the subject matter of job-related tasks and performance as related to the use of accounting information system. The study will aid the future business environment by obtaining employee feedback regarding future changes to the system that will address their specific roles and responsibilities so that the system promotes greater efficiency and will enhance performance.